IMPLEMENTASI PENDAFTARAN DOKUMEN ADMINISTRASI KEPENDUDUKAN DENGAN SISTEM ONLINE SEBAGAI UPAYA TERTIB ADMINISTRASI DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN DEMAK - M.I.S, Ardhia Regita; Mulyani, Tri; Pujiastuti, Endah (Semarang Law Review (SLR), 2021)
Registration of population administration documents as an effort to orderly administration is carried out by the government with an online system to provide convenience for the community, so this study seeks to examine the implementation of registration of the population administration documents with an online system as an effort to orderly administration at the Department of Population and Civil Registration of Demak Regency, obstacles and efforts overcome it. The research methods used are: type of sociological juridical research, analytical descriptive specifications. The data used is primary data supported by secondary data with qualitative data analysis. The results showed that the registration of family card population administration documents with an online system as an effort to orderly administration at the Demak Regency Population and Civil Registration Office in January 2017 - February 2021 was based on the Republic of Indonesia Law Number 24 of 2013 concerning Population Administration changes. on Law Number 23 of 2006 concerning Population Administration, and Regulation of the Minister of Home Affairs of the Republic of Indonesia Number 7 of 2019 concerning Online Population Administration Services with the mechanism starting with register, login, select menu, upload, send, finish. For the implementation of the registration, there were 5,472 documents. The orderliness of administrative documents after using the online system before using the online system shows that it is more orderly to use the online system, as indicated by the increasing number from year to year. The obstacles include 2 things, first, the public's lack of understanding to access online services, in this case it can be attempted by means of socialization, namely through brochures, websites, Instagram and Youtube; Second, the absence of a strong network/signal in some areas, in this case it can be attempted by serving reporters who wish to register documents directly.